Pengaruh Persepsi Risiko, Literasi Keuangan dan Media Sosial terhadap Keputusan Investasi pada Generasi Milenial - Cahayati, Lisa Eka (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Based on data from KSEI as of the end of July 2023, the number of investors in the Indonesian capital market has grown significantly to reach 11.4 million investors, growing 10.75% year-to-date (YTD). The increasing number of investors in the capital market is one of them influenced by digitalization where a lot of content is spread on social media, one of which is capital market content. The increase in the number of investors is currently dominated by the millennial generation because the millennial generation is a generation that is updated about something and has a high curiosity. This study aims to examine the effect of perceived risk, financial literacy and social media on millennial generation investment decisions in the DKI Jakarta area. This research is a quantitative study using multiple linear regression analysis with the help of the SmartPLS. The number of samples in this study were 100 respondents who came from the millennial generation in the DKI Jakarta area.